2021
DOI: 10.1039/d1cy00660f
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Lewis acid acceleration in nickel-catalysed C–H, C–C and C–O bond cleavage

Abstract: The current understanding of Lewis acid effects in transition metal catalysis is generally based on the enhanced charge transfer from metal to substrate due to the formation of Lewis acid-base...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…In preliminary experiments, although GVL was found to be able to accelerate the aerobic oxidation of isochroman, the selectivity for the desired 1-isochromanone ( P1 ) was only 61%, and for 4-isochromanone ( P′1 ) it was 39% (Table 1, entry 1). Inspired by the effect of Lewis acids on the bond dissociation energy (BDE) of the O–H bond in NHPI, 28,29 various acids and bases were tested as additives to improve the yield of 1-isochromanone (Table S1†). To our delight, these additives significantly affected the chemoselectivity and reactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary experiments, although GVL was found to be able to accelerate the aerobic oxidation of isochroman, the selectivity for the desired 1-isochromanone ( P1 ) was only 61%, and for 4-isochromanone ( P′1 ) it was 39% (Table 1, entry 1). Inspired by the effect of Lewis acids on the bond dissociation energy (BDE) of the O–H bond in NHPI, 28,29 various acids and bases were tested as additives to improve the yield of 1-isochromanone (Table S1†). To our delight, these additives significantly affected the chemoselectivity and reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the effect of Lewis acids on the bond dissociation energy (BDE) of the O-H bond in NHPI, 28,29 various acids and bases were tested as additives to improve the yield of 1-isochromanone (Table S1 †). To our delight, these additives significantly affected the chemoselectivity and reactivity.…”
Section: Aerobic Oxidation Of Isochroman Over Gvlmentioning
confidence: 99%
“…Acidbase properties of supports have been widely considered to be an important factor to influence the catalytic hydrogenolysis, especially for the adsorption and activation of CQO/C-O bonds. 9 It has been reported that acidic sites of supports participate in catalytic processes by polarizing and activating CQO bond while basic sites interact with the p* orbital of CQO bond to promote C-O/CQO hydrogenolysis. Zirconium dioxide (ZrO 2 ), as a generally known important support, has been widely studied in catalytic processes because ZrO 2 contains both acidity and basicity despite different phases.…”
Section: Introductionmentioning
confidence: 99%
“…Nezam et al used Ni/La 2 O 3 /γ-Al 2 O 3 catalysts to convert ethanol to higher alcohols at 230 °C with 75–80% selectivity. However, a high dehydrogenation rate and the ability to break C–C/C–O bonds by metallic Ni boost the conversion, leading to the formation of byproducts such as methane (CH 4 ), carbon monoxide (CO), and carbon dioxide (CO 2 ). The byproduct formation lowers the yields of higher alcohols.…”
Section: Introductionmentioning
confidence: 99%